2015
DOI: 10.1371/journal.pone.0140894
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Propagation of Uterine Electrophysiological Signals Recorded with a Multi-Sensor Abdominal Array in Term Pregnancies

Abstract: The objective of this study was to quantify the number of segments that have contractile activity and determine the propagation speed from uterine electrophysiological signals recorded over the abdomen. The uterine magnetomyographic (MMG) signals were recorded with a 151 channel SARA (SQUID Array for Reproductive Assessment) system from 36 pregnant women between 37 and 40 weeks of gestational age. The MMG signals were scored and segments were classified based on presence of uterine contractile burst activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The mechanical contraction of the uterus is commonly measured with tocodynamometry ( Bakker et al, 2010 ). The electrophysiological activity of the uterus, including increase in synchronization of the myometrial activity and propagation of the contractile activity, can be measured either electrically ( Buhimschi et al, 1997 , Terrien et al, 2010 , De Lau et al, 2013 ) or magnetically ( Eswaran et al, 2002 , Ramon et al, 2005 , Escalona-Vargas et al, 2015 , Govindan et al, 2015 ). Although they are quite useful, these analyses have been limited to the sensor level.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical contraction of the uterus is commonly measured with tocodynamometry ( Bakker et al, 2010 ). The electrophysiological activity of the uterus, including increase in synchronization of the myometrial activity and propagation of the contractile activity, can be measured either electrically ( Buhimschi et al, 1997 , Terrien et al, 2010 , De Lau et al, 2013 ) or magnetically ( Eswaran et al, 2002 , Ramon et al, 2005 , Escalona-Vargas et al, 2015 , Govindan et al, 2015 ). Although they are quite useful, these analyses have been limited to the sensor level.…”
Section: Discussionmentioning
confidence: 99%
“…a) Data Acquisition and Preprocessing Physionet (mmgdb) database comprised of twenty five magnetomyography signals out of which recordings from twenty four subjects used in this work [21]. The signals were recorded with 151 channel SARA (SQUID Array for Reproductive Assessment) system at University of Arkansas for Medical Sciences, Little Rock, USA [12]. The records have subject id and channel labels along with maternal information like cervical dilation, Days to delivery, BMI and Gestation Period.…”
Section: Methodsmentioning
confidence: 99%
“…The uterine contraction conduction velocity also increases at the onset of labor [11]. Escalona-Vargas et al [12] reported the uterine MMG signals of term pregnancies where the signals were quantified using the quadrant approach. As the electrical activity of the uterus increases at the onset of labor, the frequency and synchronization indices are helpful to understand the parturition process [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ECG (Electrocardiogram) sensors are highly sensitive to motion artifact, which can hinder its ubiquitous use. To improve the sensor reliability, multi-sensor or sensor array approaches are commonly used [20]. Sensor fusion techniques can then be applied to fuse information from these sensors.…”
Section: Architectural Framework Of Ibsn and Its Componentsmentioning
confidence: 99%